An update on the efficacy of oral corticosteroids in the treatment of wheezing episodes in preschool children. (December 2014) - Collins, Andrew D.; Beigelman, Avraham
Traditionally, oral corticosteroids (OCSs) have been the mainstay of treatment for acute wheezing episodes among preschool children with a history of recurrent wheezing. Although there is substantial evidence for the efficacy of OCSs as a treatment for asthma exacerbations in school-aged children and adolescents, recent clinical studies questioned the benefits of OCSs as a treatment for acute wheezing in preschool children. This review summarizes the current evidence on the efficacy of OCSs as a treatment for acute wheezing episodes among preschool age children with episodic wheezing, focusing on studies performed in three different settings: OCS treatment initiated by parents in the outpatient setting, OCS treatment initiated in the emergency department (ED), and OCS treatment among hospitalized preschool children. The results of most studies reviewed in this paper do not support the efficacy of OCS treatment among preschool children with recurrent wheezing. The heterogeneity of early childhood wheezing and asthma might be part of the explanation for lack of efficacy of this intervention noted in multiple studies.